Generation of meteorological Tsunamis (large amplitude seiches) near the Balearic and Kuril Islands - Rabinovich, Alexaander B.; Monserrat, Sebastian (1998)
Extreme atmosphere-induced seiche oscillations occasionally occur in specific inlets and bays of the world ocean causing severe damage to coastal areas, ships and port constructions. Ciutadella inlet (Menorca Island, Western Mediterranean) can be singled out as a place where such large seiches, locally known as rissaga, are quite common. Similar (although weaker) oscillations are also regularly observed in bays of Shikotan Island (South Kuril Islands, northwestern Pacific). Several spectacular events in these regions, identified in the first part of this study (Rabinovich and Monserrat, 1996), are analysed to determine the atmospheric parameters responsible for the generation of large-amplitude seiches. Their generation mechanism was shown to be quite different from that causing ordinary background oscillations. Coincidence of some external factors and certain resonance effects seem to be necessary to produce the destructive waves. In particular, rissaga waves in Ciutadella inlet were found to be related to significant atmospheric disturbances propagating from the southwest, coinciding with the orientation of the inlet, and having a phase speed of about 30 m/s, which is close to the phase speed of long waves offshore from Menorca. Pronounced resonant properties of the innter basin strongly amplify incoming waves in Ciutadella inlet. In contrast, the bays of the northwestern coast of Shikotan Island are protected from normally incident atmosphere-induced waves by the elongated Kunashir Island, hence the whole situation there is not so favorable for the excitation of large seiches. - Reproduced
Keywords: Kuril Islands; Balearic Islands; Ciutadella; Rissaga; Bottom pressure measurements; Atmospheric pressure oscillations; Harbour resource; Tsunami; Wave generation; Seiches; Long waves